HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP MAHASISWA 2018 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TENTANG PERASAN BAWANG PUTIH (ALLIUM SATIVUM L.) DALAM MENGOBATI ACNE VULGARIS - DWI WINDI ASTUTI; YENITA YENITA (LP2MTBM MAKARIOZ, 2023)
One of the compounds contained in garlic is allicin. Pharmacologically, allicin has antibacterial, antifungal, antioxidant, and anticancer properties. Allicin found in garlic is formed from organosulfur compounds, namely gamma-glutamyl-s-allyl-cysteine and sally-L-cysteine sulfoxides through enzymatic reactions with the help of the enzyme allinase. As an antibacterial Allisin works by changing the features of proteins, lipids and polysaccharides on the membrane. bacterial cells. that there is a relationship between the level of knowledge and the attitude of 2018 students of the Faculty of Medicine, University of Muhammadiyah North Sumatra regarding the juice of garlic (Allium Sativum L.) in treating acne vulgaris. The research design used is descriptive research with a cross-sectional research design where each research subject is only observed once by distributing questionnaires through the google form application. Furthermore, the results are tabulated and the data is processed using Chi-square. The results of the level of knowledge of garlic juice in treating acne vulgaris in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra Batch 2018 where sufficient knowledge is 78 people (75.7%), good knowledge 13 people (12.6%), and less knowledge 12 people 11.7%), while the results of attitudes where positive attitudes are 43 people (41,7%), and negative attitudes are 60 people (58,3%). The results of the knowledge and attitude test were analyzed by Chi-square with a value of p = 0.000 (P <0.05). There is a relationship between the level of knowledge and attitudes towards garlic juice in treating acne vulgaris in 2018 students of the Faculty of Medicine, University of Muhammadiyah North Sumatra.